(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
The article discusses anticolonial education from the theoretical contribution of bell hooks and Paulo Freire. We carry out a theoretical incursion into the works of these and other authors in order to highlight the importance of an education that recognizes and awakens two students towards an education as a practice of freedom. We present pretagogy as a proposal for classrooms in which anti-racist knowledge is considered not to be pedagogical. We understand that, for the construction of an anti-colonial education, it is necessary to change in the production of two didactic-pedagogical knowledge and skills of the school daily life. Decolonial and feminist epistemologies have provided us with clues for the execution of an increasingly democratic and equitable education.